The role of European intellectuals in the public sphere - Medeiros, Pilar Damião (2015)
This paper tries to understand – throughout a comparative social, historical and political analysis – if there is any continuity in the modus operandi of intellectuals in contemporary public arena. Thus, the main purpose of this paper is to identify, if the European public intellectual of the 21st century has recovered his/her active role and legitimacy in the public domain such as the one he/she already experienced in the mid-sixties and seventies. Having in mind the contradictory discourses around the role and representation of the intellectual, it seems, nevertheless, crucial to keep hold of E. Said’s argument about intellectuals as “representative figures” (E. Saïd, 1993), who through responsible action, creativity, courage (B. Misztal, 2007) and an “avantgardistic instinct for relevance’s” (Habermas, 2009) should be endorsed with the values of a free and deliberative democracy. In a nutshell, this paper enables us to understand that the resurgence of critical intervention and political engagement of civic-minded intellectuals in the public arena has been contributing to a greater vitality and re-politicization of European public sphere.